Factors associated with allergy traits around the 2nd year of life: a brazilian cohort study - Alessandra Karla Oliveira Amorim Muniz; Cecilia Claudia Costa Ribeiro; Elcio Oliveira Vianna; Hellen Cristina Oliveira Amorim Serra; Joelma Ximenes Prado Teixeira Nascimento; Viviane Cunha Cardoso; Marco Antonio Barbieri; Antonio Augusto Moura da Silva; Heloisa Bettiol (BMC, 2022)
Abstract Background Allergic status has been strongly influenced by early exposures; however, allergic diseases are hard to measure in early life. Thus, this study proposed a latent variable allergy traits around the second year of life and analyzed pre- and perinatal factors associated with this phenomenon. Methods The study used data from the BRISA birth cohort, Ribeirão Preto, Brazil (n = 3644). The theoretical model included: family allergy (history of allergic rhinitis, atopic dermatitis, and asthma); gestational period variables (socioeconomic status, mother's skin color, pregestational body mass index - BMI, smoking, gestational diabetes, and hypertension); birth variables (gestational age, 5-minute Apgar score, birth weight, type of delivery), and early life factor (exclusive breast feeding). The outcome was allergy traits around the 2nd year of life, a latent variable deduced from the shared variance among medical diagnosis of allergic rhinitis, atopic dermatitis, and food allergy. The model was analyzed by structural equation modeling. Results Higher socioeconomic status (SC = 0.256; p < 0.001) and higher family allergy values (SC = 1.224; p < 0.001) were associated with higher allergy trait values. Hypertension during pregnancy was associated with higher values (SC = 0.170; p = 0.022) and exclusive breast feeding (SC = -0.192; p < 0.001) with low allergy trait values. Conclusion Although socioeconomic and environmental factors were associated with allergy traits around the 2nd year of life, the family component of allergy was the exposure that best explained this outcome.